2014
DOI: 10.1074/jbc.m114.568493
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Transcription Activator CLOCK Regulates Progression through a ∼24-h Feedback Loop to Influence the Circadian Period in Drosophila

Abstract: Background: CLOCK phosphorylation coincides with circadian rhythms in transcription. Results: CLOCK phosphorylation sites are identified that regulate the timing and level of transcriptional activity and influence circadian period. Conclusion: CLOCK phosphorylation influences the circadian period by regulating transcriptional activity and progression through the circadian cycle. Significance: This study shows that CLOCK phosphorylation contributes to circadian period determination in Drosophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 59 publications
(97 reference statements)
4
44
0
Order By: Relevance
“…To test this model, we performed ChIP assays using CWO antiserum on wild-type, Clk out and per 01 flies collected at ZT2 and ZT14 in LD. In Clk out flies, which necessarily lack CLK-CYC heterodimers [33], CWO is bound to tim E-boxes at both ZT2 and ZT14 with binding signals comparable to the strong CWO binding in wild-type flies at ZT14 (Fig 5A). In contrast, in per 01 flies, which lack PER-dependent repression of CLK-CYC activation [34], low binding signals of CWO were detected at ZT2 and ZT14, indicating that PER is indeed required for CWO to bind E-boxes (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To test this model, we performed ChIP assays using CWO antiserum on wild-type, Clk out and per 01 flies collected at ZT2 and ZT14 in LD. In Clk out flies, which necessarily lack CLK-CYC heterodimers [33], CWO is bound to tim E-boxes at both ZT2 and ZT14 with binding signals comparable to the strong CWO binding in wild-type flies at ZT14 (Fig 5A). In contrast, in per 01 flies, which lack PER-dependent repression of CLK-CYC activation [34], low binding signals of CWO were detected at ZT2 and ZT14, indicating that PER is indeed required for CWO to bind E-boxes (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, NEMO over-expression decreases CLK levels and consequently delays PER and TIM accumulation and causes long period. Recently, it was found that CLK is phosphorylated at >15 sites in cell culture [36,37]. Mutation of all of these sites to alanine (CLK-15A) results in hypo-phosphorylated CLK, which has increased stability and transcriptional activity.…”
Section: Post-translational Controlmentioning
confidence: 99%
“…These daily activity patterns were highly similar to the daily activity patterns of Clk out ( Fig. 2D) and Clk Jrk flies, neither of which expresses functional dCLK protein (33)(34)(35). Under constant dark conditions, the p{dClk-Δ},2M;Clk out flies showed dampened morning and evening activity peaks with delayed phases, whereas the p{dClk-Δ},4M;Clk out flies did not manifest evident peaks of activity ( Fig.…”
Section: Results Dclk Internally Deleted For Aa657-707 (Dclk-δ) Showsmentioning
confidence: 48%